2008
DOI: 10.1109/tmag.2008.2001664
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes and Hysteresis Losses in Fe-Doped GdSiGe

Abstract: Magnetocaloric Gd 5 Si 2 Ge 2 -based alloys exhibit a well-documented giant magnetocaloric effect at around room temperature. However, as candidate materials for real-world refrigeration devices, they suffer from a number of problems, one of which is large hysteresis losses while cycling in and out of the magnetic field. It has, however, been reported that a small amount of iron reduces these hysteresis losses very significantly, so increasing the total potential cooling capacity of the material. We have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The Curie temperatures of the Ga-substituted alloys correspond to the second-order transition of the O(I) phase ($299 K). The substitution of Si by Fe, however, does not suppress the structural transition in Gd 5 Si 2Àx Fe x Ge 2 alloys but instead promotes the formation of the 5:3 phase (Podmiljšak et al, 2008(Podmiljšak et al, , 2009a. Magnetocaloric properties of the Gd 5 Si 2 Ge 1.9 Ga 0.1 sample, which according to the X-ray powder diffraction analysis contained $81% of the 5:4 major phase, $4% of the 1:1 phase, and $15% of the 5:3 phase, were studied by means of heat capacity and direct magnetocaloric measurements (Palacios et al, 2010a).…”
Section: Magnetic Properties Magnetocaloric Effect and First-order mentioning
confidence: 98%
“…The Curie temperatures of the Ga-substituted alloys correspond to the second-order transition of the O(I) phase ($299 K). The substitution of Si by Fe, however, does not suppress the structural transition in Gd 5 Si 2Àx Fe x Ge 2 alloys but instead promotes the formation of the 5:3 phase (Podmiljšak et al, 2008(Podmiljšak et al, , 2009a. Magnetocaloric properties of the Gd 5 Si 2 Ge 1.9 Ga 0.1 sample, which according to the X-ray powder diffraction analysis contained $81% of the 5:4 major phase, $4% of the 1:1 phase, and $15% of the 5:3 phase, were studied by means of heat capacity and direct magnetocaloric measurements (Palacios et al, 2010a).…”
Section: Magnetic Properties Magnetocaloric Effect and First-order mentioning
confidence: 98%
“…3a In magnetism, 4 a wide range of applications can be found starting from the storage of information 4a to nanoelectronics and spintronics 4d and also magnetocaloric materials, designing new alloys allowing cooling. 5 Among these materials cobalt NCs are of particular interest due to their unique magnetic properties. Indeed cobalt NCs exist in three crystalline forms, hcp (hexagonal close-packed), fcc (facecentered cubic) and ε-cobalt; the first one being the most interesting in terms of magnetic properties due to its high magnetocrystalline anisotropy.…”
mentioning
confidence: 99%
“…Though most investigation were made for Ge substitution, a significant reduction in Δ|S M | because of the suppression of the structural transformation has been observed so it is suggested that Si and Ge should be substituted simultaneously for Fe and Sn doping as can be seen in Table 3 [15,[28][29][30][31]. A small substitution with iron (substituting for 5% of the germanium, otherwise it will have deleterious effect on MCE properties and minimal effect on reducing hysteresis losses [28,30]) reduced the losses by 90% thus resulting in 20%-50% higher RCP value, though it overall reduced the Δ|S M | to only one-third of its original value [27,29,30]. The T C of the matrix phase cess.…”
mentioning
confidence: 99%